Amputation and prosthetics of the lower extremity: The 2020 Dutch evidence-based multidisciplinary guideline. Issue 1 (15th February 2023) - Fard, Behrouz; Persoon, Saskia; Jutte, Paul C.; Daemen, Jan-Willem H.C.; Lamprou, D-A A.; Hoope, Werner Ten; Prinsen, Erik C.; Houdijk, Han; Olsman, Jeroen; Holling, Tobias; De Wever, Heike P.P.R.; Schrier, Ernst; et al.
Abstract : Background: Lower-limb amputations are rare but debilitating events in the lives of affected persons. Treatment of persons with amputation inherently involves many different health care professions at different stages leading to and after an amputation. There are prevailing clinical questions within the work field related to different facets of care including peri/postoperative aspects, prosthetic components, rehabilitation treatment, and health care processes. Objectives: To provide an up-to-date multidisciplinary evidence-based guideline for health care professionals involved in the treatment of persons with lower-limb amputation in the Netherlands. Methods: Identification of key questions in a focus group, systematic review of the evidence (up to March 2019, using Embase and MEDLINE databases), and weighing considerations, culminating in clinical recommendations. Results: Twelve key questions were formulated. Recommendations of two key questions were upheld in line with the previous 2012 guideline. Ten systematic literature searches were performed, leading to the inclusion of 59 studies. Conclusion: A summary of evidence-based conclusions, considerations, and recommendations of the 2020 guideline is presented.